IESC-Child: An Interactive Emotional Children's Speech Corpus. (January 2020) - Pérez-Espinosa, Humberto; Martínez-Miranda, Juan; Espinosa-Curiel, Ismael; Rodríguez-Jacobo, Josefina; Villaseñor-Pineda, Luis; Avila-George, Himer
Highlights: The design of a method to induce emotions in children from 6 to 11 years old based on the interaction with a robot in a Wizard of Oz scenario. The analysis of the emotional content obtained from the recorded sessions. The analysis of the reliability of the labeling based on the measurement of the agreement between the raters. Abstract: In this paper, we describe the process that we used to create a new corpus of children's emotional speech. We used a Wizard of Oz (WoZ) setting to induce different emotional reactions in children during speech-based interactions with two robots. We recorded the speech spoken in Mexican Spanish by 174 children (both sexes) between 6 and 11 years of age. The recordings were manually segmented and transcribed. The segments were then labeled with two types of emotional-related paralinguistic information: emotion and attitude. The corpus contained 2093 min of audio recordings (34.88 h) divided into 19, 793 speech segments. The Interactive Emotional Children's Speech Corpus (IESC-Child) can be a valuable resource for researchers studying affective reactions in speech communication during child-computer interactions in Spanish and for creating models to recognize acoustic paralinguistic information. IESC-Child is available to the research community upon request.